Laminated board with heat insulation performance and preparation method thereof
By laying glass fiber fabric on the surface of the infrared shielding layer of the laminate and combining thermosetting resin, the problem of reducing light transmittance caused by direct mixing of tungsten bronze powder and resin is solved, and a composite material with high heat insulation, high light transmittance and high strength is achieved.
Patent Information
- Application Number
- CN202510056846.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, the direct mixing of tungsten bronze with resin can easily lead to a decrease in light transmittance of the laminate, and the mechanical strength and tensile resistance of the thermoplastic material are insufficient, which cannot meet the rigid requirements of the heat insulation material.
By forming an infrared shielding layer on the surface of the first substrate, and laying glass fiber fabric on the surface, combining a thermosetting resin, tungsten bronze powder and the thermosetting resin are combined by transfer method to prevent agglomeration, and reducing the refractive index through the filler in the thermosetting resin to improve light transmittance.
A composite material with high heat insulation, high light transmittance and high strength is achieved, which avoids the black spot problem caused by the agglomeration of tungsten bronze powder, improves the quality and aesthetics of the laminate, and enhances its mechanical properties.
Smart Images

Figure CN119858329A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a laminate with heat insulation performance and a preparation method thereof. Background Art
[0002] With the increasing awareness of energy conservation and environmental protection, the demand for composite materials with high thermal insulation, high light transmittance and high strength is gradually increasing in the fields of construction, transportation and energy. Although traditional laminates have good mechanical properties, they have limitations in thermal insulation, light transmittance and comprehensive heat shielding performance.
[0003] Infrared radiation is one of the main forms of heat transmission. Blocking infrared radiation can significantly reduce the heat loss of materials. As a functional material, tungsten bronze (MWO3) has attracted extensive attention due to its excellent near-infrared shielding ability and visible light transmittance.
[0004] In the prior art, by directly applying tungsten bronze coating on glass products, it can play a certain role in heat insulation, but because tungsten bronze is dark blue, it often affects the light transmittance of glass products, thereby affecting the light transmittance of glass products. In addition, by evenly mixing thermoplastic materials with tungsten bronze to prepare a curing glue with thermal conductivity, its heat insulation performance can be improved to a certain extent, but thermoplastic materials usually have low mechanical strength and tensile resistance, and cannot meet the rigidity requirements of heat insulation materials.
[0005] Therefore, it is extremely urgent to prepare a composite material with high thermal insulation, high light transmittance and high strength in the fields of construction and even transportation. Summary of the invention
[0006] One purpose of the first aspect of the present invention is to provide a method for preparing a laminate with high thermal insulation and high light transmittance, so as to solve the technical problem in the prior art that direct mixing of tungsten bronze and resin during the preparation of thermal insulation laminates easily leads to reduced light transmittance of the laminates.
[0007] Another object of the first aspect of the present invention is to further improve the quality of the laminate.
[0008] The second aspect of the present invention aims to provide a laminated board prepared according to the above preparation method.
[0009] According to the purpose of the first aspect of the present invention, the present invention provides a method for preparing a laminate with high thermal insulation and high light transmittance, comprising:
[0010] forming an infrared shielding layer on the pretreated surface of the first substrate;
[0011] Laying at least one glass fiber fabric on the surface of the infrared shielding layer;
[0012] Covering the surface of the glass fiber fabric with a second substrate to enclose the infrared shielding layer and the glass fiber fabric in a sealed cavity between the first substrate and the second substrate;
[0013] When the sealed cavity reaches a preset pressure, the thermosetting resin is poured, and after the pouring is completed, the cavity is left to stand for a preset time to prepare the laminate; wherein,
[0014] The infrared shielding layer is made of tungsten bronze powder, the molecular formula of which is MWO3, where M is any one of Li, Na, K, Rb or Cs, and the volume fraction of the glass fiber fabric in the high-strength laminate is any value in the range of 10%-50%.
[0015] Optionally, the thermosetting resin includes epoxy resin, a curing agent and a filler, and the mass ratio of the filler to the epoxy resin is any value in the range of 0.1%-9.0%.
[0016] Optionally, the preset pressure is any value in the range of -0.01 MPa to -0.2 MPa.
[0017] Optionally, before the step of forming an infrared shielding layer on the pretreated surface of the first substrate, the method further comprises:
[0018] Coating a sodium alginate coating of a preset thickness on the surface of the first substrate;
[0019] The sodium alginate film layer is dried to obtain the first substrate with the sodium alginate film layer coated on the surface.
[0020] Optionally, before the step of covering the surface of the glass fiber fabric with a second substrate, the method further includes:
[0021] The release agent is coated on the surface of the first substrate for multiple times, and a drying time is allowed between two adjacent coatings of the release agent.
[0022] Optionally, the chemical formula of the tungsten bronze powder in the infrared shielding layer is CsWO3, and the molar ratio of the Cs element to the W element in the tungsten bronze powder is any value in the range of 1:1-1:3.
[0023] Optionally, the M in the laminate x The mass fraction of WO3 is any value between 1.0wt% and 5.5wt%.
[0024] Optionally, the preset time is any value in the range of 24h-48h.
[0025] According to the purpose of the second aspect of the present invention, the present invention also provides a laminate with heat insulation performance, the laminate comprises an infrared shielding layer, at least one glass fiber fabric and a thermosetting resin, the infrared shielding layer is made of tungsten bronze powder, and the infrared shielding layer is formed on one side surface of the laminate by spraying or transfer, the thermosetting resin comprises epoxy resin, curing agent and filler, and the volume fraction of the glass fiber fabric in the high-strength laminate is any value in the range of 10%-50%; wherein,
[0026] The laminate is prepared according to any one of the preparation methods described above.
[0027] The present invention is to form a glass fiber fabric impregnated with a thermosetting resin doped with infrared shielding nanoparticle tungsten bronze by integrated molding, so that the tungsten bronze powder with infrared shielding performance is combined with the thermosetting resin by transfer printing without mixing the tungsten bronze powder with the thermosetting resin, so as to prevent the tungsten bronze powder from agglomerating when mixed with the thermosetting resin, so that the agglomerated tungsten bronze is impregnated in the gaps of the glass fiber fabric and cannot be evenly distributed, thereby avoiding the agglomerated tungsten bronze from forming black spots visible to the naked eye in the glass fiber fabric, thereby improving the quality and aesthetics of the laminate, and at the same time, the filler in the thermosetting resin can gradually reduce the refractive index of the thermosetting resin to a refractive index close to that of the glass fiber fabric during its curing process, so that the glass fiber fabric is hidden in the sample, thereby improving the light transmittance of the laminate.
[0028] Furthermore, the preset pressure of the present invention is any value in the range of -0.01Mpa to -0.2MPa. By setting the pressure in the sealed cavity before the thermosetting resin is infused within the above range, it can not only ensure that the infused thermosetting resin will not generate bubbles in the glass fiber fabric, but also prevent the thermosetting resin from being infused too slowly or unable to be infused due to the low vacuum pressure in the sealed cavity, thereby improving the infusion efficiency of the thermosetting resin and ensuring the production quality of the laminate.
[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Hereinafter, some specific embodiments of the present invention will be described in detail in an exemplary and non-limiting manner with reference to the accompanying drawings. The same reference numerals in the accompanying drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the accompanying drawings:
[0031] Figure 1 is a schematic control flow chart of a method for preparing a laminate according to an embodiment of the present invention;
[0032] Figure 2 is a schematic flow chart of a method for preparing a laminate according to one embodiment of the present invention;
[0033] Figure 3 is a schematic flow chart of a first substrate preprocessing according to an embodiment of the present invention;
[0034] Figure 4 is a schematic microscopic morphology diagram of a first substrate after spraying of a CsWO3 dispersion according to an embodiment of the present invention;
[0035] Figure 5 is a light-transmitting picture of a laminate curing process according to an embodiment of the present invention;
[0036] Figure 6 is a graph of tensile strength and tensile modulus of laminates with different amounts of glass fiber fabric according to one embodiment of the present invention;
[0037] Figure 7 is a roughness measurement result diagram of a laminate under a three-dimensional confocal microscope according to an embodiment of the present invention;
[0038] Figure 8 is a photograph of the visible light transmittance of a laminate according to one embodiment of the present invention;
[0039] Fig. 9 is a visible light-transmittance spectrum diagram of the laminated boards prepared in Example 8 and Comparative Example 2 of the present invention;
[0040] Fig.10 It is a visible light-infrared projection spectrum data diagram of the laminated boards in Inventive Example 1, Example 8, Example 9 and Comparative Example 2;
[0041] Fig.11 is a visual photograph of the laminate prepared in Comparative Example 1 of the present invention;
[0042] Fig.12 This is a visual photograph of the laminate prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0043] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0044] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0045] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.
[0046] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0047] Figure 1 is a schematic control flow chart of a method for preparing a laminate according to an embodiment of the present invention, Figure 2 is a schematic flow chart of a method for preparing a laminate according to an embodiment of the present invention, Figure 3 is a schematic flow chart of a first substrate preprocessing according to an embodiment of the present invention, Figure 4 is a schematic microscopic morphology diagram of the first substrate after spraying of CsWO3 dispersion according to one embodiment of the present invention, Figure 5 is a light-transmitting picture of the curing process of a laminate according to an embodiment of the present invention, Figure 6 is a graph of tensile strength and tensile modulus of laminates with different amounts of glass fiber fabric according to one embodiment of the present invention, Figure 7 is a roughness measurement result diagram of a laminate under a three-dimensional confocal microscope according to an embodiment of the present invention, Figure 8 is a photograph of the visible light transmittance of a laminate according to one embodiment of the present invention.
[0048] like Figure 1 As shown, the present invention provides a method for preparing a laminate with thermal insulation performance, comprising:
[0049] Step S100: forming an infrared shielding layer on the pre-treated surface of the first substrate;
[0050] Step S200: laying at least one glass fiber fabric on the surface of the infrared shielding layer;
[0051] Step S300: Covering the surface of the glass fiber fabric with a second substrate to seal the infrared shielding layer and the glass fiber fabric in a sealed cavity between the first substrate and the second substrate;
[0052] Step S400: When the sealed cavity reaches a preset pressure, a thermosetting resin is poured, and after the pouring is completed, it is left to stand for a preset time to prepare a laminate, wherein the material of the infrared shielding layer is tungsten bronze powder, the molecular formula of the tungsten bronze powder is MWO3, M is any one of Li, Na, K, Rb or Cs, the thermosetting resin includes epoxy resin, curing agent and filler, and the mass ratio of filler to epoxy resin is any value in the range of 0.1%-9.0%.
[0053] In the present embodiment, in the method for preparing the laminated board, the first substrate is firstly pretreated, and the MWO3 dispersion is sprayed on the surface of the pretreated first substrate, and the MWO3 dispersion is dried to form an infrared shielding layer, and then at least one glass fiber fabric is laid on the surface of the infrared shielding layer, and then the second substrate is covered on the surface of the glass fiber fabric to seal the infrared shielding layer and the glass fiber fabric in a sealed cavity between the first substrate and the second substrate, and the sealed cavity is evacuated, and when the sealed cavity reaches a preset pressure, a thermosetting resin is poured, and after the thermosetting resin is poured, it is left to stand for a preset time to prepare the laminated board (refer to Figure 2 Here, the number of the glass fiber fabrics can be one, two or more, and the MWO3 dispersion is a mixed solution of MWO3 and ethanol solvent.
[0054] In this embodiment, a glass fiber fabric is impregnated with a thermosetting resin doped with infrared shielding nanoparticle tungsten bronze by integrated molding, so that the tungsten bronze powder with infrared shielding performance is combined with the thermosetting resin by transfer without mixing the tungsten bronze powder with the thermosetting resin, so as to prevent the tungsten bronze powder from agglomerating when mixed with the thermosetting resin, resulting in the agglomerated tungsten bronze being impregnated in the gaps of the glass fiber fabric and being unable to be evenly distributed, thereby avoiding the agglomerated tungsten bronze from forming black spots visible to the naked eye in the glass fiber fabric, thereby improving the quality and aesthetics of the laminate, and at the same time, the filler in the thermosetting resin can gradually reduce the refractive index of the thermosetting resin to a refractive index close to that of the glass fiber fabric during its curing process, so that the glass fiber fabric is hidden in the sample, thereby improving the light transmittance of the laminate.
[0055] like Figure 4As shown, in this embodiment, the device for spraying the MWO3 dispersion is an automatic spraying device. Before the automatic spraying device sprays the MWO3 dispersion, the spraying flow rate and air pressure are adjusted to the target requirements. Then, the automatic spraying device runs the spraying of the MWO3 dispersion according to the imported spraying path curve diagram, thereby uniformly spraying the MWO3 dispersion of a preset thickness on the first substrate to form an infrared shielding layer that meets the thermal insulation performance of the laminate after it dries. Here, the vertical distance between the nozzle and the first substrate when the automatic spraying device sprays the MWO3 dispersion is any value in the range of 5cm-15cm. By controlling the vertical distance between the nozzle and the first substrate, the spraying uniformity of different spraying materials is controlled, that is, the vertical distance can be 5cm, 8cm, 10cm, 12cm or 5cm, or any value in the range of 5cm-15cm.
[0056] In this embodiment, the mass ratio of the filler to the epoxy resin is any value in the range of 0.1%-9.0%, that is, the mass ratio of the filler to the epoxy resin in the thermosetting resin can be 0.1%, 0.1%, 0.1%, 0.1%, 0.1%, 0.1%, or 0.1%, or any value in the range of 0.1%-9.0%. By controlling the mass ratio of the filler to the epoxy resin in the thermosetting resin within the above range, it is ensured that during the curing process of the thermosetting resin, the filler can reduce the refractive index of the thermosetting resin to match the refractive index of the glass fiber fabric, thereby improving the light transmittance of the laminate (refer to Figure 5 ). Here, the filler may be methyl methacrylate.
[0057] In this embodiment, the molecular formula of the tungsten bronze powder is MWO3, where M is any one of Li, Na, K, Rb or Cs, that is, the tungsten bronze powder can be any one of lithium tungsten bronze, sodium tungsten bronze, potassium tungsten bronze, rubidium tungsten bronze or cesium tungsten bronze. Due to the different types of M elements in the tungsten bronze powder, different tungsten bronze powders can be formed, and the infrared shielding properties of the corresponding tungsten bronze powders are different due to different types of M elements. The corresponding tungsten bronze powder can be selected according to the needs, which is not limited here.
[0058] In a preferred embodiment, the chemical formula of the tungsten bronze powder in the infrared shielding layer is CsWO3, that is, the tungsten bronze powder includes Cs element, and the material of the infrared shielding layer is cesium tungsten bronze, which has a non-stoichiometric ratio and a special oxygen octahedral structure, so that the cesium tungsten bronze powder has low resistivity, low-temperature superconducting properties and excellent near-infrared absorption properties.
[0059] In this embodiment, the preparation method of cesium tungsten bronze includes the following steps:
[0060] Weigh a first preset mass of WCl6 powder and a second preset mass of CsOH-H2O powder;
[0061] The weighed WCl6 powder and CsOH-H2O powder were dissolved in anhydrous ethanol and mechanically stirred at room temperature to form a slightly yellow clear solution;
[0062] adding acetic acid and PVP to the clear solution to form a first reaction solution;
[0063] The first reaction solution is transferred to a stainless steel polytetrafluoroethylene lined reactor, sealed and placed in a high temperature oven for heating and reaction;
[0064] The product was taken out and washed with deionized water and ethanol for multiple times, respectively, until no chloride ions were present in the product;
[0065] The washed product is transferred to a vacuum drying oven for drying to obtain dark blue nano cesium tungsten bronze powder, wherein the molar ratio of the Cs element to the W element in the cesium tungsten bronze powder is any value in the range of 1:1-1:3.
[0066] In this embodiment, in the preparation method of cesium tungsten bronze powder, WCl6 powder and CsOH-H2O powder are first weighed and dissolved in anhydrous ethanol, and then mechanically stirred at room temperature to make the powder completely dissolved and evenly dispersed to form a slightly yellow clear solution, and then acetic acid and PVP are added to the clear solution to form a first reaction solution, and the first reaction solution is transferred to a stainless steel polytetrafluoroethylene lined reactor, which is sealed and placed in a high-temperature oven for heating and reaction. After the reaction is completed and the reactor is cooled to room temperature, the product is taken out and washed with deionized water and ethanol for multiple times until there is no chloride ion in the product, and then the washed product is transferred to a vacuum drying oven for drying to obtain a dark blue nano cesium tungsten bronze powder.
[0067] In this embodiment, the molar ratio of the Cs element and the W element in the cesium tungsten bronze powder is any value in the range of 1:1-1:3, that is, the molar ratio of the Cs element and the W element in the cesium tungsten bronze powder can be 1:1, 1:1.5, 1:2, 1:2.5 or 1:3, or any value in the range of 1:1-1:3. When the molar ratio of the Cs element and the W element in the cesium tungsten bronze powder is within the above range, the infrared shielding layer can effectively absorb and reflect infrared radiation, so that the infrared shielding layer has good infrared absorption capacity in a wider band, thereby improving the infrared shielding performance of the laminate. When the molar ratio of the Cs element and the W element in the cesium tungsten bronze powder is less than 1:3, since the W element content in the cesium tungsten bronze powder is too high at this time, the color of the cesium tungsten bronze powder is darker, which reduces the light-seeking performance of the laminate. When the molar ratio of Cs element to W element in the cesium tungsten bronze powder is greater than 1:1, the infrared shielding performance of the laminate is reduced, that is, the thermal insulation performance of the laminate is reduced, because the W element content in the cesium tungsten bronze powder is too low. In other embodiments, the cesium tungsten bronze powder can also be obtained by commercial purchase.
[0068] In the preparation method of the thermosetting resin in this embodiment, the epoxy resin, filler and curing agent are firstly mixed uniformly according to a preset ratio to form a thermosetting resin mixed solution, and then the bubbles generated in the thermosetting resin mixed solution are removed by vacuum defoaming to prevent the quality of the laminate from being affected by the inability to eliminate the bubbles after the thermosetting resin containing bubbles is poured into the sealed cavity. Here, the pressure value of the vacuum defoaming is -0.03Mpa.
[0069] In a further embodiment, the volume fraction of the glass fiber fabric in the high-strength laminate is any value in the range of 10%-50%, that is, the volume fraction of the glass fiber fabric in the high-strength laminate can be 10%, 20%, 30%, 40% or 50%, or any value in the range of 10%-50%. By setting the volume fraction of the glass fiber fabric in the high-strength laminate within the above range, the fiber content in the laminate is moderate, that is, the mechanical properties of the laminate can be enhanced and its tensile strength can be improved, while also ensuring that the laminate has a high light transmittance.
[0070] In this embodiment, the glass fiber fabric is made of E-alkali-free glass fiber cloth, and each glass fiber fabric is woven from bundles of glass fibers overlapped at 45 degrees, with a gram weight of 50g / m 2 , multiple layers of glass fiber fabric are superimposed at 0° or 90°, that is, when multiple layers of glass fiber fabric are laid on the first substrate, they are laid in a 0° or 90° superimposed manner, so as to improve the mechanical strength and tensile strength of the laminate while also improving its light transmittance to a certain extent.
[0071] In this embodiment, the number of glass fiber fabrics is any value between 1 and 25, that is, the number of glass fiber fabrics can be 1, 3, 5, 10, 15, 20 or 25, or any value between 1 and 25. The tensile strength and tensile modulus of the laminate are controlled by adjusting the number of glass fiber fabrics, that is, as the number of glass fiber fabrics increases, the tensile strength and tensile modulus of the corresponding laminate gradually increase (refer to Figure 6 ).
[0072] In other embodiments, when the volume fraction of the glass fiber fabric in the high-strength laminate is less than 10%, the limiting content in the laminate is too low to significantly improve or enhance the mechanical strength of the laminate, and cannot meet the mechanical strength and tensile resistance of the laminate. When the volume fraction of the glass fiber fabric in the laminate is greater than 50%, the fiber content in the high-strength laminate is too high, and the refractive index matching degree of the glass fiber fabric with too high fiber content cannot be met during the curing process of the thermosetting resin, thereby affecting the light transmittance of the laminate.
[0073] In a further embodiment, the preset pressure is any value in the range of -0.01Mpa to -0.2MPa, that is, the pressure in the sealed cavity before the thermosetting resin is poured can be -0.01Mpa, -0.015Mpa, -0.05Mpa, -0.1Mpa, -0.15Mpa or -0.2Mpa, or any value in the range of -0.01Mpa to -0.2MPa. In this embodiment, by setting the pressure in the sealed cavity before the thermosetting resin is poured within the above range, it can be ensured that the poured thermosetting resin will not generate bubbles in the glass fiber fabric, and the thermosetting resin will not be poured too slowly or cannot be poured due to the low vacuum pressure in the sealed cavity, thereby improving the pouring efficiency of the thermosetting resin, thereby ensuring the production quality of the laminate and improving the production efficiency of the laminate.
[0074] like Figure 3 As shown, in a further embodiment, before step S100, the following steps are further included:
[0075] Coating a sodium alginate coating with a preset thickness on the surface of the first substrate;
[0076] The sodium alginate film layer is dried to obtain a first substrate with the sodium alginate film layer coated on the surface.
[0077] In this embodiment, a sodium alginate coating of a preset thickness is firstly coated on the surface of the first substrate, and then the sodium alginate film layer is dried to obtain the first substrate with the sodium alginate film layer coated on the surface. Here, the preset thickness is 300 μm, the drying temperature is 60° C., and the drying time is 2 hours.
[0078] In this embodiment, the first substrate is pretreated by coating a sodium alginate film layer on the first substrate. Since sodium alginate has strong hydrophilicity, when the MWO3 dispersion is sprayed on the sodium alginate film layer, the sodium alginate film layer will adsorb the ethanol molecules in the MWO3 dispersion, thereby evenly distributing the MWO3 dispersion on the surface of the sodium alginate film layer, further improving the dispersion uniformity of MWO3 in the MWO3 dispersion, thereby improving the thermal insulation uniformity of the infrared shielding layer of the laminate.
[0079] like Figure 7 As shown, further, since there is no chemical interaction between the MWO3 in the MWO3 dispersion and the ammonium alginate film layer and the thermosetting resin, during the curing process of the thermosetting resin, the tightening effect of the matrix in the thermosetting resin during the hybridization reaction provides sufficient matrix rigidity, and the transferred MWO3 particles are highly anchored in the matrix by physically capturing the nanoparticles, so that the surface roughness of the prepared laminate is extremely low, and the doped MWO3 nanoparticles in the high-strength laminate are stably dispersed in the thermosetting resin.
[0080] In a further embodiment, before step S300, the following steps are further included:
[0081] The release agent is coated on the surface of the second substrate for multiple times, and a drying time is allowed between two adjacent coatings of the release agent.
[0082] In this embodiment, before placing the second substrate on the laid glass fiber fabric, the second substrate is coated with a release agent multiple times, and a preset time is left between two adjacent release agent coatings so that another layer of release agent is coated after one layer of release agent is dried, so that the release agent can be evenly distributed on the surface of the second substrate, preventing the injected thermosetting resin from adhering to the surface of the second substrate not coated with the release agent, causing adhesion when the laminate is demolded. Here, the drying time is 10 minutes.
[0083] In a further embodiment, the mass fraction of MWO3 in the laminate is any value between 1.0wt% and 5.5wt%, that is, the mass fraction of MWO3 in the laminate can be 1.0wt%, 2.0wt%, 3.0wt%, 4.0wt% or 5.5wt%, or any value between 1.0wt% and 5.5wt%. In this embodiment, by setting the mass fraction of MWO3 within the above range, it is ensured that after the ethanol solvent in the MWO3 dispersion is completely volatilized, the remaining MWO3 powder can be transferred to the thermosetting resin to form an infrared shielding layer with high infrared shielding performance, thereby ensuring the high thermal insulation of the laminate.
[0084] In a further embodiment, the preset time is any value in the range of 24h-48h, and the curing time after the thermosetting resin is poured into the sealed cavity can be 24h, 30h, 36h, 42h or 48h, or any value in the range of 24h-48h. In this embodiment, the curing time after the thermosetting resin is poured into the sealed cavity is set within the above range, which can not only ensure that the thermosetting resin can be completely cured, but also prevent its curing time from being too long to affect the production efficiency of the laminate.
[0085] In this embodiment, a spacer of preset thickness is provided between the first substrate and the second substrate, i.e., in the sealed cavity, and the thickness of the spacer is adjusted to control the distance between the first substrate and the second substrate, thereby adjusting the thickness of the prepared laminate. Here, the thickness of the spacer can be 0.5 mm, 1.0 mm, or 2.0 mm, so as to prepare a laminate with a thickness ranging from 0.5 mm to 2.0 mm.
[0086] The method for preparing the laminate provided by the present invention has the characteristics of simple process, mild reaction conditions, easy operation, low energy consumption, and green and pollution-free, and can also realize large-scale continuous production.
[0087] The present invention also provides a laminate with high heat insulation and high light transmittance, the laminate includes an infrared shielding layer, at least one glass fiber fabric and a thermosetting resin, the infrared shielding layer is made of tungsten bronze powder, and the infrared shielding layer is formed on one side of the laminate by spraying or transfer, the thermosetting resin includes epoxy resin, curing agent and filler, and the volume fraction of the glass fiber fabric in the high-strength laminate is any value in the range of 10%-50%, wherein the high-strength laminate is prepared according to the above preparation method. Here, the preparation method of the laminate is not repeated here.
[0088] In this embodiment, by impregnating a thermosetting resin into a glass fiber fabric coated with an infrared shielding layer on one side, the thermosetting resin is completely impregnated into the glass fiber fabric, and at the same time, the infrared shielding layer on one side of the glass fiber fabric is adsorbed into the glass fiber fabric and the thermosetting resin by transfer, thereby forming an infrared shielding layer on one side of the laminate that can improve the thermal insulation performance. At the same time, during the curing process of the thermosetting resin, the presence of the filler can gradually reduce the refractive index of the thermosetting resin until it is the same as the refractive index of the glass fiber fabric, thereby making the prepared laminate have higher light transmittance and higher mechanical strength.
[0089] In this embodiment, the laminate not only has high thermal insulation performance and strong light transmittance, but also has high mechanical strength, that is, the laminate of this embodiment can simultaneously achieve good near-infrared shielding effect, high visible light transmittance and strong tensile strength, ensuring that the laminate can efficiently utilize sunlight and ensure sufficient natural lighting. At the same time, the thermal insulation performance and light weight and high light transmittance of the laminate can also reduce carbon emissions from the aspect of weight reduction, so that it can be widely used in the field of energy loss reduction. Here, the field of energy loss reduction includes the fields of construction, transportation and so on.
[0090] The present application will be further described in detail below with reference to specific embodiments.
[0091] In some embodiments, the first substrate is pretreated, and a MWO3 dispersion is sprayed on the pretreated surface of the first substrate. The MWO3 dispersion can be synthesized by itself or purchased commercially. After the MWO3 dispersion is dried, an infrared shielding layer is formed. Then, 1 to 25 sheets of glass fiber fabric are laid on the surface of the infrared shielding layer. Then, a second substrate is covered on the surface of the glass fiber fabric. A release agent is coated on the second substrate, and the thickness of the spacer between the first substrate and the second substrate is any value between 0.5 mm and 2.0 mm, so as to shield the infrared The outer shielding layer and the glass fiber fabric are enclosed in a sealed cavity between the first substrate and the second substrate, and then when the sealed cavity reaches a preset pressure, the preset pressure is any value in the range of -0.01Mpa to -0.2MPa, a thermosetting resin is poured, the mass fraction of the filler in the thermosetting resin is any value in the range of 0.1%-9.0%, and after the pouring is completed, it is left to stand for any value of 24h-48h to prepare a laminate, and the mass fraction of CsWO3 in the laminate is any value in the range of 1.0wt%-5.5wt%.
[0092] Example 1
[0093] First, the first substrate is pretreated, and CsWO3 dispersion is sprayed on the pretreated surface of the first substrate. After the CsWO3 dispersion is dried, an infrared shielding layer is formed. The CsWO3 dispersion is obtained by self-synthesis, and the dispersant is ethanol solvent. Then, 5 glass fiber fabrics are laid on the surface of the infrared shielding layer, and then the second substrate is covered on the surface of the glass fiber fabric. The second substrate is coated with a release agent, and the pad thickness is 1mm, so as to seal the infrared shielding layer and the glass fiber fabric in a sealed cavity between the first substrate and the second substrate. Then, when the sealed cavity reaches -0.04Mpa, thermosetting resin is poured, and the mass fraction of the filler in the thermosetting resin is in the range of 7.0%. After the pouring is completed, it is left to stand for 48 hours to prepare a laminate. The mass fraction of CsWO3 in the laminate is 3.12wt%.
[0094] Example 2
[0095] The only difference between Example 2 and Example 1 is that the number of sheets of glass fiber fabric is 15 and the thickness of the pad is 2 mm.
[0096] Example 3
[0097] The only difference between Example 3 and Example 1 is that the preset pressure of the sealing cavity is -0.06 MPa.
[0098] Example 4
[0099] The only difference between Example 4 and Example 1 is that the CsWO3 dispersion is purchased commercially, the dispersion modifier is Digo755 dispersion modifier, and the preset pressure of the sealed cavity is -0.06 MPa.
[0100] Example 5
[0101] The only difference between Example 5 and Example 1 is that the volume fraction of the filler is 3.0%, the CsWO3 dispersion is purchased commercially, the dispersion modifier is BYK dispersion modifier, and the thickness of the pad is 0.5 mm.
[0102] Example 6
[0103] The only difference between Example 6 and Example 1 is that the CsWO3 dispersion is purchased commercially, the dispersion modifier is SN5040 dispersion modifier, and the preset pressure of the sealed cavity is -0.06 MPa.
[0104] Example 7
[0105] The only difference between Example 7 and Example 1 is that the volume fraction of the filler is 5.0% and the thickness of the pad is 0.5 mm.
[0106] Example 8
[0107] The only difference between Example 8 and Example 1 is that the number of glass fiber fabrics is 10, the thickness of the pad is 2.0 mm, the preset pressure of the sealed cavity is -0.06 MPa, and the mass fraction of CsWO3 in the high-strength laminate is 1.1 wt%.
[0108] Example 9
[0109] The only difference between Example 9 and Example 1 is that the number of sheets of glass fiber fabric is 25, the preset pressure of the sealed cavity is -0.02 MPa, and the mass fraction of CsWO3 in the high-strength laminate is 5.2 wt%.
[0110] Example 10
[0111] The only difference between Example 10 and Example 1 is that the preset pressure of the sealing cavity is -0.08 MPa.
[0112] Comparative Example 1
[0113] The difference between Comparative Example 1 and Example 1 is that after the CsWO3 dispersion and the thermosetting resin are uniformly mixed, they are infused by a vacuum infusion process.
[0114] Comparative Example 2
[0115] The only difference between Comparative Example 2 and Example 1 is that the high-strength laminate does not include an infrared shielding layer made of CsWO3.
[0116] Comparative Example 3
[0117] The only difference between Comparative Example 3 and Example 1 is that the infrared shielding layer is directly formed on the first substrate without any pretreatment.
[0118] First, the thickness, Cs x The WO3 doping amount, glass fiber content, light transmittance, tensile strength and infrared shielding rate were tested and the results are shown in Table 1.
[0119] Table 1. Performance parameters of the laminates prepared in Examples 1-10 and Comparative Example 1
[0120]
[0121] As shown in Table 1, it can be found from the experimental data of the above embodiments 1-10 that the heat-insulating high-strength laminate obtained by the above technical solution of the present invention has a high light transmittance (such as Figure 8 As shown) and high infrared shielding performance, while balancing the mechanical strength and thermal insulation performance, and the preparation process is simple and easy to achieve large-scale production.
[0122] In other embodiments, the inventors also conducted experiments with other raw materials and conditions listed in this specification with reference to the preparation methods of Examples 1-10, for example, spraying infrared particles 4 times and also preparing a series of heat-insulating high-strength laminates. It was found through testing that these heat-insulating high-strength laminates also have the high light transmittance and a certain degree of infrared shielding effect described in this specification, and the strength is also the same.
[0123] Next, the transmittance of the laminates prepared in Example 8 and Comparative Example 2 was characterized within the wavelength range of visible light. Fig. 9 It is a visible light-transmittance spectrum diagram of the laminated board prepared in Example 8 and Comparative Example 2 of the present invention.
[0124] like Fig. 9 As shown in the figure, within the visible light wavelength range, the transmittance of the laminate with tungsten bronze powder added is close to that of the ordinary laminate without tungsten bronze powder added, which means that the addition of tungsten bronze powder will not significantly reduce the transmittance of the laminate, but also improve the infrared shielding rate of the laminate.
[0125] Next, the transmittance of the laminates prepared in Example 1, Example 8, Example 9 and Comparative Example 2 in visible light was characterized. Fig.10 It is a visible light-infrared projection spectrum data diagram of the laminated boards in Inventive Example 1, Example 8, Example 9 and Comparative Example 2.
[0126] like Fig.10As shown, the transmittance of Example 1, Example 8, and Example 9 in the visible light wavelength range is close to the transmittance of Comparative Example 2, and the transmittance of Example 1, Example 8, and Example 9 in the near-infrared light wavelength range is significantly different from the transmittance of Comparative Example 2, indicating that the transmittance of the laminate prepared by spraying and transferring in combination with a thermosetting resin is close to the transmittance of the laminate without adding tungsten bronze powder, further illustrating that the infrared shielding layer formed by spraying and transferring will not affect the transmittance of the laminate, and can improve the infrared shielding performance of the traditional laminate.
[0127] like Fig.11 As shown in the data of Comparative Example 1 in Table 1, after the CsWO3 dispersion is evenly mixed with the thermosetting resin, the thickness, transmittance and infrared shielding rate of the same laminate prepared by vacuum infusion process are unevenly distributed. This is because the cesium tungsten bronze powder cannot form a uniform dispersion with the resin due to its own weight and surface properties. After the thermosetting resin is mixed with the glass fiber fabric, the powder will be stuck in the fiber texture inside the glass fiber, causing the powder to agglomerate again in a large area, resulting in the cesium tungsten bronze powder being unable to be evenly distributed in the laminate, thereby seriously affecting the light transmittance and aesthetics of the laminate.
[0128] like Fig.12 As shown, an infrared shielding layer is directly formed on the surface of the first substrate that has not been pretreated, and a subsequent vacuum infusion step of a thermosetting resin is performed, i.e., the thermosetting resin directly contacts the first substrate, so that the thermosetting resin directly adheres to the first substrate during the curing process, resulting in the inability to smoothly demold the cured laminate, causing texture and debonding to appear on the laminate, thereby seriously affecting the quality of the laminate.
[0129] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0130] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a laminate with heat insulation performance, characterized in that: include: forming an infrared shielding layer on the pretreated surface of the first substrate; Laying at least one glass fiber fabric on the surface of the infrared shielding layer; Covering the surface of the glass fiber fabric with a second substrate to enclose the infrared shielding layer and the glass fiber fabric in a sealed cavity between the first substrate and the second substrate; When the sealed cavity reaches a preset pressure, the thermosetting resin is poured, and after the pouring is completed, the cavity is left to stand for a preset time to prepare the laminate; wherein, The infrared shielding layer is made of tungsten bronze powder, the molecular formula of which is MWO3, where M is any one of Li, Na, K, Rb or Cs, and the volume fraction of the glass fiber fabric in the high-strength laminate is any value in the range of 10%-50%.
2. The preparation method according to claim 1, characterized in that: The thermosetting resin comprises epoxy resin, a curing agent and a filler, and the mass ratio of the filler to the epoxy resin is any value in the range of 0.1%-9.0%.
3. The preparation method according to claim 2, characterized in that: The preset pressure is any value in the range of -0.01 MPa to -0.2 MPa.
4. The preparation method according to claim 3, characterized in that: Before the step of forming an infrared shielding layer on the pretreated surface of the first substrate, the step further includes: Coating a sodium alginate coating of a preset thickness on the surface of the first substrate; The sodium alginate film layer is dried to obtain the first substrate with the sodium alginate film layer coated on the surface.
5. The preparation method according to claim 4, characterized in that: Before the step of covering the surface of the glass fiber fabric with a second substrate, the step further includes: The release agent is coated on the surface of the first substrate for multiple times, and a drying time is allowed between two adjacent coatings of the release agent.
6. The preparation method according to claim 5, characterized in that: The chemical formula of the tungsten bronze powder in the infrared shielding layer is CsWO3, and the molar ratio of the Cs element to the W element in the tungsten bronze powder is any value in the range of 1:1-1:
3.
7. The preparation method according to any one of claims 1 to 6, characterized in that The mass fraction of the MWO3 in the laminate is any value between 1.0wt% and 5.5wt%.
8. The preparation method according to claim 7, characterized in that: The preset time is any value between 24h-48h.
9. A laminate with heat insulation properties, characterized in that: The laminate comprises an infrared shielding layer, at least one glass fiber fabric and a thermosetting resin, wherein the infrared shielding layer is made of tungsten bronze powder and is formed on one side of the laminate by spraying or transfer, the thermosetting resin comprises epoxy resin, a curing agent and a filler, and the volume fraction of the glass fiber fabric in the high-strength laminate is any value in the range of 10%-50%; wherein, The laminate is prepared according to the preparation method according to any one of claims 1-8.